ANALISIS FAKTOR EKONOMI YANG MEMPENGARUHI JUTAAN ANAK PUTUS SEKOLAH PENDIDIKAN DASAR INDONESIA - Sulfiani, Besse; Nurhayati; Syahrani Astuti, Nia; Sulfiana; Andi Ardani, Mutiara Cahya Puspita; Hasrianti; Dzaky Arif, Muh. Fadhil; Panessai, Muhammad Kesnal Ramdan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The high dropout rate in Indonesia remains a significant challenge in the education sector, especially at the primary level. Economic factors such as poverty, limited access to education, and lack of parental support are among the main contributors to this issue. This study employs a qualitative approach using literature review methods to analyze various economic factors influencing school dropouts. The research aims to identify key economic barriers and propose viable solutions to mitigate their impact on education. The findings indicate that household economic conditions, inadequate educational facilities, and limited financial support for underprivileged students are the dominant factors hindering access to education. The study concludes that increasing educational subsidies, providing targeted scholarships, and ensuring more equitable distribution of educational infrastructure are strategic measures to reduce dropout rates. Therefore, collaboration between the government, society, and private sector is essential in improving educational accessibility for all children in Indonesia.